Impact of Chronic Kidney Disease on the Processes of Care and Long‐Term Mortality of Non–ST‐Segment–Elevation Myocardial Infarction: A Nationwide Cohort Study and Long‐Term Follow‐Up - Nicholas Weight; Saadiq Moledina; Mohsin Ullah; Harindra C. Wijeysundera; Simon Davies; Nicholas W. S. Chew; Claire Lawson; Safi U. Khan; Chris P. Gale; Muhammad Rashid; Mamas A. Mamas (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background A growing population of patients with chronic kidney disease (CKD) presents with non–ST‐segment–elevation myocardial infarction, although little is known about their longer‐term mortality. Methods and Results Using the MINAP (Myocardial Ischaemia National Audit Project) registry, linked to Office for National Statistics mortality data, we analyzed 363 559 UK patients with non–ST‐segment–elevation myocardial infarction, with or without CKD. Cox regression models were fitted, adjusting for baseline demographics. Compared with patients without CKD, patients with CKD were less frequently prescribed P2Y12 inhibitors (89% versus 86%, P<0.001) less likely to undergo invasive angiography (67% versus 41%, P<0.001) or percutaneous coronary intervention (41% versus 25%, P<0.001), and were less often referred to cardiac rehabilitation (80% versus 66%, P<0.001). Following non–ST‐segment–elevation myocardial infarction, patients with CKD had higher risk of 30‐day (adjusted hazard ratio [HR], 1.24 [95% CI, 1.20–1.29], 1‐year 1.47 [95% CI, 1.44–1.51]) and 5‐year mortality 1.55 (95% CI, 1.53–1.58) than patients without CKD (all P<0.001). Risk of mortality over the entire study period was highest in CKD Stage 5 (HR, 2.98 [95% CI, 2.87–3.10]), even after excluding mortality ≤30 days (HR, 3.03 [95% CI, 2.90–3.17]) (P<0.001). There was no significant difference in proportion of deaths attributable to cardiovascular disease at 30 days (CKD; 76% versus no CKD; 76%), or 1 ‐year (CKD; 62% versus no CKD; 62%). Conclusions Patients with CKD were significantly less likely to receive invasive investigation or undergo percutaneous coronary intervention and had significantly higher risk of short‐ and longer‐term mortality. Risk of mortality increased with reducing CKD stage. Cardiovascular disease was the main cause of mortality in patients with CKD, but at comparable rates to the general population with non–ST‐segment–elevation myocardial infarction.